Influence of glycerol and added fat on finishing pig performance - A W Duttlinger; Michael D Tokach; Jim L Nelssen; Robert D Goodband; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2008)
A 28-d study was conducted to determine the influence of dietary glycerol on grow-finish pig performance. The experiment was conducted at a commercial swine research facility in southwest Minnesota. A total of 1,093 pigs (initially 171.3 lb, PIC) were blocked by weight and randomly allotted to 1 of 6 dietary treatments. Pigs were fed corn-soybean meal-based diets. The treatments were arranged in a 2 × 3 factorial with main effects of glycerol (0, 2.5, or 5%) and added fat (0 or 6%). Overall (d 0 to 28), there was a fat × glycerol interaction (P<0.04) for ADFI. When 5% glycerol was added to diets without added fat, ADFI decreased; however, ADFI did not change when glycerol was added to diets containing 6% added fat. Pigs fed diets with added fat had improved (P<0.01) ADG and F/G compared with pigs fed diets with no added fat. Increasing glycerol decreased ADG (linear, P<0.02) and ADFI (linear, P<0.04) and tended (linear, P<0.08) to worsen F/G, a result of the negative effect of adding glycerol to diets without fat. In conclusion, 6% added fat improved ADG and F/G, but the glycerol used in this study decreased ADG and ADFI when added to diets without added fat.; Swine Day, 2008, Kansas State University, Manhattan, KS, 2008
Keywords: Swine day; 2008; Kansas Agricultural Experiment Station contribution; no. 09-074-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1001; Fat; Glycerol; Swine